PENGARUH THE BIG FIVE PERSONALITYDAN MATERIALISME KONSUMEN TERHADAP PEMBELIAN IMPULSIF SERTA DAMPAKNYA PADA PEMBELIAN KOMPULSIF (SURVEY PADA PENGUNJUNG MALL DI KOTA BANDUNG) - Raeni Dwisanty (Indonesian Journal of Economics and Business, 2012)
Lately the rapid  development of ritel modern business, such as mall and plaza at various city in the country is undeniedable has changed spending pattern of indonesian consumers.It is related to the factors of personality and life style, such as the changes of life style and habit of shopping . In fact, consumers often don’t think rationally in determining the most important staffs they need.There are several consumers’ reasons to purchase the products, such as: killing the bad mood, expressing identity, or just having fun.This research is purposed to get the result from: description study of The Big Five Personality, consumers’ materialism, impulsive and compulsive purchasing towards mall visitors in Bandung; Analysis of influence of The Big Five Personality and Consumers’ Materialism towards compulsive purchasing of mall visitors in Bandung.The methods used in this research are descriptive and verificative methods. The data collection techniques are literature and field studies. The field study uses observation, interview, and questioner. Sample is taken from 300 mall visitors in Bandung. The withdrawal of sample uses Systematic Random Sampling. Influence model is analyzed by using Structural Equation Model.As the result of this research, there is influence of The Big Five Personality and consumers’ materialism towards impulsive buying of mall visitors in Bandung in which the most dominant factor influences the impulsive buying is Neuroticism. Nevertheless, the less factor influences the impulsive buying is Agreeableness. This research also shows that there is influence of The Big Five Personality, consumers’ materialism, and impulsive buying towards compulsive buying of mall visitors in Bandung in which the most influence factor towards compulsive buying is agreeableness and impulsivebuying  whereas the less influence factor is conscientiousness.